2018
DOI: 10.1007/s12195-018-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lipid Signaling Mediators for Mesenchymal Stem Cell Mobilization During Bone Repair

Abstract: Our studies suggest that MSC mobilization through S1PR3 antagonism is a promising strategy for endogenous tissue engineering and improving MSC delivery to treat bone diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…SLs are a highly diverse family of molecules which are important building blocks of eukaryotic membranes 33 . Prior to this work, we demonstrated that modulating novel sphingosine-1-phosphate (S1P) and S1P receptor 3 (S1PR3) signaling mobilizes both hematopoietic stem cells (HSCs) and MSCs to enhance ectopic bone growth, further emphasizing the importance of understanding SL functions 46,47 . In this study, we performed LC-MS/MS to characterize AD-, BM-, and UCT-MSCs sphingolipid metabolism profiles.…”
Section: Discussionmentioning
confidence: 99%
“…SLs are a highly diverse family of molecules which are important building blocks of eukaryotic membranes 33 . Prior to this work, we demonstrated that modulating novel sphingosine-1-phosphate (S1P) and S1P receptor 3 (S1PR3) signaling mobilizes both hematopoietic stem cells (HSCs) and MSCs to enhance ectopic bone growth, further emphasizing the importance of understanding SL functions 46,47 . In this study, we performed LC-MS/MS to characterize AD-, BM-, and UCT-MSCs sphingolipid metabolism profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary to our results, previous studies have shown that S1PR3 overexpression alone is sufficient to induce myeloid differentiation in human HSC 38 . In addition, S1PR3 has been implicated in the mobilization from the bone marrow to the peripheral blood of hematopoietic and mesenchymal progenitors 39,40 . The decreased efficiency of in vitro monocyte maturation, and relative increase in the fraction of bone marrow CD14 + monocytes with reciprocal decrease of bone marrow CD16 + neutrophils of engrafted mice, may suggest that S1PR3 both plays cell autonomous roles in monocytes during maturation as well as impacts the trafficking of myeloid cells from bone marrow stores to circulating cells in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis, S1P receptors, which are chemotactically sensitive to S1P gradients, regulate multiple processes, including migration, matrix adhesion, and cell-cell contact. Therefore, the steep gradient of S1P concentration existing between bone marrow and blood might promote monocytes to navigate from the bone marrow to circulation 40 . The biological contributions of S1PR3 to monocyte maturation and trafficking may be complex and could merit future dedicated study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this hypothesis, S1P receptors, which are chemotactically sensitive to S1P gradients, regulate multiple processes, including migration, matrix adhesion, and cell-cell contact. Therefore, the steep gradient of S1P concentration existing between bone marrow and blood, may drive cell types including monocytes, to navigate from the bone marrow to circulation 40 .…”
Section: Discussionmentioning
confidence: 99%